International Watercourses Law and A Perspective on Nepal-India Cooperation - Sangroula, Yubaraj (Kathmandu School of Law Review, 2013)
Water is unequivocally essential for life; simply not possible without it. The Greeks were astute enough to acknowledge it as the primal substance of universe, some 2500 years ago. Water is a resource for dignified life, as much as it is a bare necessity. Explaining the ‘development’ and ‘survival’ aspect of water requires a deeper thinking, analysis and projection of ideas thereof. The book authored by Suryanath Upadhyay is an apt example in which the author has rightly projected that Nepal boasts abundance of water resource in it territory but sadly, the ordinary citizens have not been able to reap much from the abundance.